Religious School Education in Chile, From the Conquest of Abya Yala to Today: A Historical Journey - Pérez Barría, Claudio Hernán (2024)
This article provides a historical journey that begins with the conquest and colonization of Abya Yala to the present. At the start of the trajectory, the systematic violence exercised by the European invaders towards the inhabitants of the aforementioned territory is made visible, which had an effect on the epistemological and symbolic dimensions, physically and ideologically subjugating the original cultures, with consequences that are still evident to this day, this being visible in the Chilean educational system in general, and, specifically, in religious school education, which inherit and therefore prolong the colonizing episteme, thus a decolonizing action is imperatively proposed.